Sistem Pembelajaran Bahasa Arab di Lembaga Kursus dan Pelatihan (LKP) Bahasa Arab Nurul Iman Parung-Bogor - Hakim, Lukmanul (Ta'limi | Journal of Arabic Education and Arabic Studies, 2023)
This article aims to discuss the Arabic language learning system at the Nurul Iman Parung Arabic Course and Training Institute (LKP), Bogor. Today, many people are interested in studying Arabic, seeing the urgency of Arabic as a solution to various complex problems in modern times. Many educational institutions participate in developing and implementing Arabic language learning, both formal and non-formal. One of these educational institutions is the Al-Ashriyyah Islamic Boarding School Nurul Iman Parung Bogor, which established an Arabic language LKP in Parung Bogor. This research is a field research (field research) in the form of qualitative research using a multidisciplinary approach which includes, among others: pedagogical, normative theological, juridical, sociological, and psychological approaches. The results of this study suggest that LKP Nurul Iman Arabic conducts Arabic courses for students who wish to deepen and further develop their Arabic language skills through non-formal institutions specifically established for the development of Arabic. The Arabic language learning system at LKP Nurul Iman Arabic is a non-credit Arabic learning program run by the Language Development Institute for all students who are interested in learning Arabic further. LKP Arabic Nurul Iman has not been equipped with standard curriculum references, syllabi, and manuals, teaching materials are tentative/change according to management policies every year. The learning model is designed simultaneously on the same day and hour in each class, it is not allowed to shift teaching hours or days by the teacher, this course program also does not make the class the only learning center. LKP Arabic Nurul Iman has succeeded in improving students' Arabic language skills, and has also succeeded in producing sufficiently qualified Arabic language experts. The increased achievement of Arabic competitions at the Al Ashriyyah Nurul Iman Islamic Boarding School, such as Arabic speech contests, Arabic debate competitions, Taqdimul Qisshoh and others, both at the district and national levels, is evidence of the increased students' Arabic language skills